Intelligent Monitoring of Grey Oyster Mushroom Cultivation with IoT - Kumar C., Anil; Shrinivasan, Lakshmi; Kumar R., Anil; S., Harish; Vaishnavi D. A., Lavanya (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Classifications of Mushrooms as vegetables in the food world are not accurate as they belong to the fungi kingdom. Mushrooms provide several important nutrients like protein, vitamins, minerals, and antioxidants. They become important part of Indian food market. Cultivation of mushrooms fills the lack in nutrient contents among the people and also helps to recycle the wastes produced by the agriculture in India. Grey oyster mushroom is the one which can be grown artificially for commercial purposes. Cultivation of grey oyster mushrooms by manual methods, require lot of time and labor. And the labors have to maintain the hygiene and cleanliness. Also, environment conditions have to be maintained. All these things handling manually are difficult and yield lesser production. To make things simpler and improve the production, this paper proposes an intelligent system for monitoring of grey oyster mushroom cultivation using IOT. In this system we are continuously monitoring the environment conditions in the spawn mycelium growing room by using sensors and microcontroller and it is informed to the farmer through the IOT. This system continuously monitors and controls the indoor (spawn mycelium growing room) environment to provide good yield and it is informed to the farmer through the IOT. ATMega328 Microcontroller gives real-time monitoring and controlling of all these environmental parameters, which helps in maintaining the required environment for the growth of grey oyster mushroom with IoT.